Doing Knowledge Online Learning Model in Media Production-Based Subjects: High and Low Students’ Prior Knowledge Analysis - Rezi Ulya Fauziah; Mujahidah Auliya Ihsani; Jakfar Shodiq (Journal of Sustainable Educational Technology and Innovation, 2026)
Background: Technological innovations have transformed education by integrating digital tools and constructivist principles, fostering interactive and adaptive learning environments. Despite these advancements, challenges persist, particularly in hands-on subjects like media production, where traditional models often fail to bridge theory and practice.Aims: This study proposed the doing knowledge online learning model, designed to enhance media production education through active learning and social interaction. Methods: To evaluate the validity and effectiveness of the proposed model, the ADDIE Model was used as the instructional design framework, and a quasi-experimental design was employed for its implementation. A total of 80 students were assigned to two groups: the experimental group using the doing knowledge online learning model and the control group using the conventional learning model. Result: Results indicated that experts rated the model with a 93% agreement, classifying it as "very good," indicating its high suitability for educational use. Additionally, students who learned with the doing knowledge online learning model had significantly better learning performance than those who learned with the conventional learning model. Moreover, even when categorized by high and low prior knowledge, students in the doing knowledge online learning model consistently outperformed their peers in the conventional learning group.Conclusion: The doing knowledge online learning model is a valid and effective approach for improving students' learning outcomes in media production and has the potential to support more engaging and practice-oriented online learning.